Controle do lançamento tributário pelos conselhos de contribuintes: segurança, moralidade e confiança - Bernardo Motta Moreira (2012)
This work focuses on control limits of the analysis of tax assessments by Administrative Courts. It discusses the history of tax administrative proceedings in the Brazilian juridical order and the importance of its improvement in the context of a complex society. The present reasoning derives from the assumption that administrative processuality is essential to state power legitimacy, to reduction of social complexity, to effectively implement democracy and even to tax consent. Therefore, measures taken by Brazilian Tax Authorities in order to contest, either through administrative hierarchical appeal or through a judicial measure, decisions issued at the end of regular tax administrative proceedings, conflict with administrative morality, legal security and stability, which should be provided by the administrative proceedings. These issues are closely linked to the impossibility of Administrative Courts reviewing arguments about the constitutionality of a certain legislative act. For this analysis, it is essential to consider the division of functional competences among the Powers of the Brazilian Republic and the protection of legal security, which must prevail in our democratic State. Whereas the protection of trust is considered as trust in the juridical order, it can be fairly assumed that a decision of the Brazilian Supreme Court eliminating the presumption of constitutionality of a given legislation authorizes and requires Administrative Courts not to apply said legal rule, under possible State liability otherwise.